2014
DOI: 10.1002/cncr.28794
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the magnitude of colorectal cancers prevented during the era of screening: 1976 to 2009

Abstract: There has been a significant decline in the incidence of colorectal cancer in the United States, particularly for late-stage disease, during a time of increasing rates of screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 40 publications
0
67
2
Order By: Relevance
“…Several studies have estimated the potential contribution of screening to decreases in CRC incidence and mortality in the United States. 3,4,25,26 The current study estimates of screening benefits appear to be somewhat smaller than noted by Ladabaum and Song 25 and larger than those from Edwards et al 3 and Yang et al 4 This is likely due to different study designs or periods, and differences in assumptions regarding the effectiveness of colonoscopy screening. For colonoscopy, the effectiveness of screening is less well established than for other recommended screening tests due to the absence of evidence from randomized controlled trials.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Several studies have estimated the potential contribution of screening to decreases in CRC incidence and mortality in the United States. 3,4,25,26 The current study estimates of screening benefits appear to be somewhat smaller than noted by Ladabaum and Song 25 and larger than those from Edwards et al 3 and Yang et al 4 This is likely due to different study designs or periods, and differences in assumptions regarding the effectiveness of colonoscopy screening. For colonoscopy, the effectiveness of screening is less well established than for other recommended screening tests due to the absence of evidence from randomized controlled trials.…”
Section: Discussioncontrasting
confidence: 65%
“…1 Registry data from the past decade indicate that both disease incidence and mortality decreased by approximately 3% per year, 2 largely due to the increased use of screening. 3,4 Despite the effectiveness of screening and the availability of various screening options, only 58% of US adults aged 50 to 75 years had received guideline-recommended testing in 2013. 5 Previous studies have demonstrated that a substantial percentage of CRC deaths are attributable to nonuse of screening.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor subsite was classified as either distal colon and rectum (C185, C186, C187, C199, and C209) or proximal colon (C180, C181, C182, C183, and C184). Previous studies have shown distal colon cancer to be more sensitive to screening, 4 …”
Section: Study Populationmentioning
confidence: 99%
“…Most of the decline in CRC incidence has been attributed to increased rates of screening through colonoscopy and sigmoidoscopy, although changes in risk factors and better treatments likely contributed to the decline. 1,4,18 These types of screening, which includes the removal of adenomatous polyps, have been shown to reduce both CRC incidence and mortality. 18 Despite evidence of its effectiveness, Hispanic men are less likely than white men to undergo endoscopic screening, and Hispanic men in California are no exception.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%
See 1 more Smart Citation